Steps of Transformational Leadership by School Principals to Enhance Educator Quality in Early Childhood Education Institutions - Rosyida Nurul Anwar (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
PAUD educators hold professional positions, which means they must maintain a high level of professionalism due to their constant interaction with students. The challenges faced by PAUD (Early Childhood Education) educators can hinder the achievement of quality education. The leadership of the PAUD principal plays a significant role in enhancing the quality of educators. This study aims to identify the steps taken by the principal’s transformational leadership to improve educator quality. The research was conducted at Al Irsyad Islamic Kindergarten in Madiun. A qualitative approach was employed, using a case study method. Data collection involved observations, interviews, and documentation. The survey results indicate that enhancing the quality of educators through transformational leadership requires specific steps in leadership transformation. Key actions include determining task priorities, assessing educator readiness, reviewing performance, and formulating a vision. Quality PAUD educators are essential for producing quality students, ultimately contributing to the development of a glorious generation in the future.